Dependence on Media and the Formation of the Level of the Academic Elite’s Knowledge concerning United Nations’ Affairs (A research based on a doctoral thesis) - عبد الامير علي عبد الهادي; الشمري علي جبار (ALBAHITH ALALAMI, 2015)
The UN organization is considered one of the most important organizations at the international level. It has accomplished multiple tasks and roles of many different issues and events that hit the developing and advanced world countries. It has performed a series of procedures and laws that have had an impact on ending the wars and conflicts that plagued some countries and continued for a period of time in the past. Moreover, it has improved the level of the international relations between a number of countries due to the problems and incidents took place between them. It has relied on finding solutions and treatments for humanitarian problems such as the preservation of the environment, preventing the spread of epidemics and diseases This study has come up with several results, most notably are the following: 1. The results of the study have shown that (258) of the sample has indicated that they spend 1-3 hours a day following up the media. 2. The academic elite has pointed out that the activity performed by the UN is a political one in that it has ranked first with (349) and a percentage of (%73.31).